Genetic Variability of Arabidopsis thaliana Mature Root System Architecture and Genome-Wide Association Study - Deja-Muylle, Agnieszka; Opdenacker, Davy; Parizot, Boris; Motte, Hans; Lobet, Guillaume; Storme, Veronique; Clauw, Pieter; Njo, Maria; Beeckman, Tom (Frontiers in Plant Science, 2022)
Root System Architecture (RSA) has a direct influence on the efficiency of nutrient uptake and plant growth, but the genetics of RSA are often only studied at the seedling stage. To get insight into the genetic blueprint of a more mature RSA, we exploited natural variation and performed a detailed in vitro study of 241 Arabidopsis thaliana accessions using large petri dishes. A comprehensive analysis of 17 RSA traits showed high variability among the different accessions unveiling correlations between traits and conditions of the natural habitat of the plants. A sub-selection of these accessions were grown in water-limiting conditions in a rhizotron set-up, which revealed that especially the spatial distribution showed a high consistency between in vitro and ex vitro conditions, while in particular a large root area in the lower zone favored drought tolerance. The collected RSA phenotype data, obtained through exhaustive measurements of RSA traits on, in contrast to earlier reports, more mature Arabidopsis accessions, were used to perform Genome Wide Association Studies (GWAS). As a result, we found not only a number of genes involved in lateral root development or auxin signaling pathways to be associated with RSA traits, but also new candidate genes that are potentially involved in adaptation to the natural habitats.